Biosynthesis of Silver Nanoparticles by Rhamnolipid produced by Pseudomonas fluorescens MFS 1 from Mangrove Soil - Govindammal, M (International Journal of Pharmaceutical & Biological Archive, 2015)
Biosynthesis of Silver Nanoparticles by Rhamnolipid produced by Pseudomonas fluorescens MFS 1 from Mangrove Soil